Yellowstone. Season 4 [videorecording (DVD)] - Sheridan, Taylor; Linson, John (Paramount, 2022)
Who shot John Dutton? That's the burning question that left fans reeling in the explosive season three finale. Following the brutal attacks on Kayce, Beth, and John Dutton, and with their fates unknown, Rip and the other wranglers wield their own brand of justice to take revenge and defend the Dutton legacy. This season digs deeper than ever into the rich Yellowstone history with flashbacks featuring Tim McGraw and Faith Hill (stars of the Yellowstone prequel 1883). Includes all ten hour-long episodes of the Emmy-nominated series, plus behind-the-scenes featurettes, an extended making-of piece, and never-before-seen interviews with cast and crew.